The Effect of Water's Cations on the Consolidation Settlement Process of Clay with Kaolinite - Ghareh, S.; Kazemian, Sina; Vahid Mojtahed Sistani, S.; Shayan Mehr, A. (ELSEVIER SCIENCE BV, 2018)
Due to high effect on stability of construction, settlement is very important factor in construction and foundation engineering. Before implementing any project, we should determine the potential of soil in terms of the amount and type of settlement. In saturated clays, water loss from soil performs after a long time (due to low permeability and high water absorption) causes high settlements which are named settlements of consolidations. In this research, experimental study of changes in the initial consolidation settlement process on kaolinite clay (kaolinite) by oedometer test, with the addition of solved cations with concentrations of 50, 150 and 300 Mg/lit (milligrams per liter) in saturated water. Research findings show that application of aluminum (Al+3), magnesium (Mg+2), calcium (Ca+2), sodium (Na+ ) and potassium (K+ ) cations with different concentrations changes the initial consolidation settlement values in appropriation with the concentration and type of cations. The highest reduction in initial consolidation settlement of kaolinite valued at 30.29% related to the sample made with cations magnesium with concentration of 300 Mg/lit.